THE PROCESS OF DEVELOPING SOCIAL COMPETENCE OF STUDENTS DURING THE EDUCATIONAL PROCESS - Farhod Makhsiddinovich Norbo’tayev; Ahmadova Farxunda Shuhratovna (Journals Park Publishing, 2022)
The article provides information on the mechanisms of successful organization of the educational process, the development of students' social competences in general educational institutions.
Keywords: competence, student, socialization, development, educational process